2018
DOI: 10.3866/pku.whxb201802261
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Mechanisms in the Thermal Decomposition of CL-20 Revealed by ReaxFF Molecular Dynamics Simulations

Abstract: The thermal decomposition of condensed CL-20 was investigated using reactive force field molecular dynamics (ReaxFF MD) simulations of a super cell containing 128 CL-20 molecules at 800-3000 K. The VARxMD code previously developed by our group is used for detailed reaction analysis. Various intermediates and comprehensive reaction pathways in the thermal decomposition of CL-20 were obtained. Nitrogen oxides are the major initial decomposition products, generated in a sequence of NO2, NO3, NO, and N2O. NO2 is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 23 publications
6
37
0
Order By: Relevance
“…We observed some bimolecular reactions, such as N 2 O 3 producing reactions, as well as intermolecular O transfer reactions (between two CL-20 molecules, or between HMX and NO 2 ), which were also reported in the decomposition of RDX. 50 These bimolecular reactions were not observed in large quantities during thermal decomposition of CL-20, [15][16][17][47][48][49]51 due to weak intermolecular interaction induced by the low stability of CL-20. 17 Thus, those bimolecular reactions are probably caused by large electric force of CEF.…”
Section: Electric Field Effect In Initial Reaction Mechanismmentioning
confidence: 99%
“…We observed some bimolecular reactions, such as N 2 O 3 producing reactions, as well as intermolecular O transfer reactions (between two CL-20 molecules, or between HMX and NO 2 ), which were also reported in the decomposition of RDX. 50 These bimolecular reactions were not observed in large quantities during thermal decomposition of CL-20, [15][16][17][47][48][49]51 due to weak intermolecular interaction induced by the low stability of CL-20. 17 Thus, those bimolecular reactions are probably caused by large electric force of CEF.…”
Section: Electric Field Effect In Initial Reaction Mechanismmentioning
confidence: 99%
“…In addition to the classical MD simulations, ab initio or first-principle molecular dynamics and reactive force field (ReaxFF) molecular dynamics [698], which enable to describe chemical reactions more precisely, have recently appeared as new members in the family of MD simulations. Using the ReaxFFMD simulations, for example, it is revealed that the formation and shear of interfacial bridge bonds lead to atom-by-atom removal of substrate materials, and the effect of tribochemical reactions caused by water molecules or OH groups has been investigated [699][700][701].…”
Section: Simulationmentioning
confidence: 99%
“…Yin et al 2 parameterized a semiempirical density functional tight-binding (DFTB) model to study deposition of carbon on copper surface. At the atomic level, Ren et al 3 simulated the thermal decomposition of highenergy-density materials using reactive force field, and Wang et al 4 reported the use of a flexible and polarizable force field to calculate vibrational frequencies of molecules on liquid surface. Combining DFT calculations and atomistic force field, Liu et al 5 studied the effect of photoisomerization on binding energy and conformation of azobenzene-containing host-guest complex.…”
Section: Sun Huaimentioning
confidence: 99%
“…The articles presented in this special issue demonstrate the roles played by molecular simulation in the cutting edge of research and development. The topics covered include CO2 reduction 1 , molecular machinery 5 , graphene chemistry 10 , carbon deposition on metal surface 2 , complex reactions 3,9 , surface chemistry 4 , polymer morphology 6 , and self-assembly 8 . Although the collection of articles is far from complete in reflecting the research activities, we hope that it is helpful especially to those researchers who are new to the field to get a snapshot of what can be achieved by using molecular simulations in materials research.…”
Section: Sun Huaimentioning
confidence: 99%